Dynamic CT but Not Optimized Multiphase CT Angiography Accurately Identifies CT Perfusion Target Mismatch Ischemic Stroke Patients - Tian, Huiqiao; Chen, Chushuang; Garcia-Esperon, Carlos; Parsons, Mark W.; Lin, Longting; Levi, Christopher R.; Bivard, Andrew (Frontiers in Neurology, 2019)
Imaging protocols for acute ischemic stroke varies significantly from center to center leading to challenges in research translation. We aimed to assess the inter-rater reliability of collateral grading systems derived from dynamic computed tomography angiography (CTA) and an optimized multiphase CTA. Also, to compare the accuracy of dynamic CTA (dCTA) and optimized multiphase CTA (omCTA) to CT perfusion (CTP) in identifying target mismatch. Acute ischemic stroke patients with a proximal large vessel occlusion underwent whole brain CTP. We assessed the status of collaterals using ASPECTS collateral system (Alberta Stroke Program Early CT Score on Collaterals) and ASITN/SIR collateral system (the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology) on dCTA and omCTA, and compared the interrater reliability using Krippendorff’s alpha and Cohen’s kappa. Eighty-one patients were included, with a median ischemic core volume of 29 mL. The collateral assessment with ASPECTS collaterals using dCTA have a similar inter-rater agreement (K-alpha: 0.71) compared to omCTA (K-alpha: 0.69). However, the agreement between dCTA and CTP in classifying patients with target mismatch was higher compared to omCTA (Kappa, dCTA: 0.81; omCTA: 0.64). We found dCTA was more accurate than omCTA in identifying target mismatch patients with proximal large vessel occlusion.